Environmental Friendliness of Freshwater Lobster (Cherax quadricarinatus) Fishing Gear in Laut Tawar Lake Based on the Code of Conduct for Responsible Fisheries (CCRF) - Rahima Nabila; Suri Purnama Febri; Siti Komariyah; Febby Hadi Setyawan (Jurnal Ilmiah Samudra Akuatika, 2025)
Laut Tawar Lake is a stagnant freshwater body located in Central Aceh Regency with an area of approximately 5,740.10 ha and has considerable fisheries potential, including freshwater lobster (Cherax quadricarinatus). The freshwater lobster is a benthic organism that inhabits rock crevices and constructs burrows in muddy substrates for shelter. The Code of Conduct for Responsible Fisheries (CCRF) provides international principles and standards to promote responsible fishing practices in order to achieve sustainable fisheries. This study aimed to assess the environmental friendliness of freshwater lobster fishing gears based on CCRF criteria. The research was conducted in December 2024 using three types of fishing gears: seruwe traps, segapa traps, and gallon traps. The results showed that the seruwe trap obtained a score of 34, the segapa trap scored 33, and the gallon trap scored 30. Based on the environmental friendliness classification of fishing gears with a score range of 28–36, all three types of fishing gears were categorized as environmentally friendly.